Molecular mechanisms of chronobiotics as functional foods - Dufoo-Hurtado, Elisa; Abraham, Wall-Medrano; Campos-Vega, Rocio (John Wiley & Sons Ltd, 2022)
The establishment of chrononutrition as an emerging topic within chronobiology has a peculiar history. Empirical observations on rhythmic “sunrise to sunset” patterns in living organisms, the object of study in chronobiology (a.k.a. circadian biology), comes from the Hippocratic era, the term desynchronosis and its relationship of environmental light and temperature with sleep patterns date from the fifties (Folk Jr,!1957). The first review on chronobiology indexed in Scopus appeared in 1920 (Halberg,!1969). Jürgen Aschoff and Collin Pittendrigh are considered the fathers of modern chronobiology with their pioneer- ing work on the natural entrainment (synchronization) of circadian (circa “around” or “approximately”, diem “day”) systems, derived from their so- called “resonance” and “bun- ker" experiments (Daan,! 2000). Konopka and Benzer (1971) were perhaps the first to report!that certain genes located in the X chromosome controls the timekeeping system in D. melanogaster, while the CLOCK (circadian locomotor output cycles protein kaput) gene reported by Takahashi in 1997 is one of the circadian genes controlling a plethora of physi- ological process (including the sleep–wake cycle) in mammals (Semenova, Madaeva, & Kolesnikova,!2021). However, the 2017!Nobel Prize in Physiology or Medicine was jointly awarded to Jeffrey Hall, Michael Rosbash, and Michael Young for their work on the mecha- nism underlying the circadian rhythm. Concurrently to modern chronobiology, chrononu- trition was also leaving its mark....